Primary antibiotic resistance of Helicobacter pylori isolates is twofold more frequent in HIV‐positive than HIV‐negative individuals: A descriptive observational study - Nkuize, Marcel (Microbiologyopen, 2021)
The antimicrobial susceptibility of Helicobacter pylori strains isolated from HIV‐positive individuals is not well characterized. This study aimed to measure the prevalence and long‐term trends associated with primary H. pylori antibiotic resistance, evaluate correlations with antibiotic consumption, and compare predictors for H. pylori antibiotic resistance between HIV‐positive and HIV‐negative individuals. In this longitudinal registry study, we evaluated consecutive adults with and without HIV infection, naïve to H. pylori treatment, who underwent upper gastrointestinal endoscopy and had a positive H. pylori culture, with susceptibility testing available, between 2004 and 2015. Outpatient antibiotic consumption data were based on nationwide aggregated numbers. H. pylori was isolated from gastric biopsies of 3008/8321 patients, 181/477 (37.9%) were HIV‐positive and 2827/7844 (36.0%) HIV‐negative. Overall cohort mean prevalence of H. pylori primary antibiotic resistance was 11.1% for clarithromycin, 17.8% levofloxacin, and 39.4% metronidazole. The prevalence of H. pylori primary resistance was significantly higher for these three drugs in HIV‐positive individuals across the study period. Linear regression showed that the prevalence of clarithromycin and levofloxacin resistance correlated with the country aggregate daily dose consumption of macrolides and quinolones, respectively. Multivariable regression analysis showed that HIV infection is a strong independent risk factor for multiple H. pylori antibiotic resistance. In summary, HIV infection is a risk factor for carrying multi‐resistant H. pylori strains and this is correlated with antibiotic consumption. Empirical therapies should be avoided in HIV‐positive individuals. These data highlight the need to implement ongoing monitoring of H. pylori antimicrobial susceptibility among HIV‐positive individuals. The study is registered at ISRCTN registry, number 13466428: https://www.isrctn.com/ISRCTN13466428.